Investigating Undergraduates’ Professionalism Expectations to The English Language Education Department Curriculum: A Case Study - Eva Freginda Feronika; Ferra Dian Andanty; Rica Sih Wuryaningrum (ELTALL: English Language Teaching, Applied Linguistic and Literature, 2025)
This qualitative case study investigates the professionalism expectations of undergraduate students in the English Language Education Department at Universitas PGRI Adi Buana Surabaya concerning their curriculum and study materials. Drawing on in-depth interviews with five graduates from batches 2017, 2018, 2019, and 2020, supplemented by curriculum documents and academic transcripts, the research identifies a significant gap between students' academic preparation and the demands of their diverse professional careers. Findings reveal that while the curriculum is generally acknowledged as a crucial roadmap for education, specific courses, most notably literature and English syntax, are widely perceived as lacking practical contribution to daily work in various fields, including teaching, tourism, transportation, administration, and hospitality. This disconnect is further exacerbated by a divergence between initial career aspirations and actual employment realities, often influenced by academic performance (GPA) and limited job market opportunities. The study highlights a clear undergraduate perspective advocating for a more practical and professionally relevant curriculum. Graduates expressed a strong desire for reduced theoretical content, increased hands-on application, and the integration of courses that directly address career readiness, job market dynamics, and professional ethics. The implications of this research underscore the critical need for the English Language Education Department to re-evaluate and adjust its curriculum to better align with the evolving needs of the workforce, thereby enhancing graduates' preparedness and competitiveness in their respective careers.